Crystal structure and Hirshfeld surface analysis of (RS)-3-hydroxy-2-{[(3aRS,6RS,7aRS)-2-(4-methylphenylsulfonyl)-2,3,3a,6,7,7a-hexahydro-3a,6-epoxy-1H-isoindol-6-yl]methyl}isoindolin-1-one - Dmitriy F. Mertsalov; Maryana A. Nadirova; Elena A. Sorokina; Marina A. Vinokurova; Sevim Türktekin Çelikesir; Mehmet Akkurt; Irina A. Kolesnik; Ajaya Bhattarai (Acta Crystallographica Section E: Crystallographic Communications, 2021)
The title compound, C24H24N2O5S, crystallizes with two independent molecules (A and B) in the asymmetric unit. In the central ring systems of both molecules, the tetrahydrofuran rings adopt envelope conformations, the pyrrolidine rings adopt a twisted-envelope conformation and the six-membered ring is in a boat conformation. In molecules A and B, the nine-membered groups attached to the central ring system are essentially planar (r.m.s. deviations of 0.002 and 0.003 Å, respectively). They form dihedral angles of 64.97 (9) and 56.06 (10)°, respectively, with the phenyl rings. In the crystal, strong intermolecular O—H...O hydrogen bonds and weak intermolecular C—H...O contacts link the molecules, forming a three-dimensional network. In addition weak π–π stacking interactions [centroid-to centroid distance = 3.7124 (13) Å] between the pyrrolidine rings of the nine-membered groups of A molecules are observed. Hirshfeld surface analysis and two-dimensional fingerprint plots were used to quantify the intermolecular interactions present in the crystal, indicating that the environments of the two molecules are very similar. The most important contributions for the crystal packing are from H...H (55.8% for molecule A and 53.5% for molecule B), O...H/H...O (24.5% for molecule A and 26.3% for molecule B) and C...H/H...C (12.6% for molecule A and 15.7% for molecule B) interactions.